Maritime VHF communications with polarization diversity over a Rician channel. (26th November 2012) - Ahn, Chang‐Jun; Jeong, Incheol; Endo, Izumi; Omori, Tatsuya; Hashimoto, Ken‐ya
SUMMARY In this paper, we propose a polarization diversity scheme to enhance maritime VHF communications. Multiple antenna systems require an antenna separation of 5–10 wavelengths to keep the correlation coefficient below 0.7 to permit the realization of space diversity. However, this may be difficult to implement in a maritime VHF system, because the maritime VHF is working in the frequency range from 156 to 174 MHz, with wavelength of approximately 2 m. On the other hand, the polarization device technique allows two co‐located antennas by using a micro‐strip technique. For this reason, the polarization technique is a practical method of attaining diversity. However, the theoretical model of polarization is very difficult and complex. Therefore, we express the cross correlation of each polarization antenna and the cross polarization discrimination of multiple polarization antennas with a simple model. Simulations show that the polarization diversity of a maritime VHF system shows better BER performance than that of the conventional reception diversity on the basis of vertical antenna with the antenna separation of 10 wavelengths. Copyright © 2012 John Wiley & Sons, Ltd.